2020
DOI: 10.1080/09712119.2020.1815752
|View full text |Cite
|
Sign up to set email alerts
|

Field synchronization of Ethiopian Highland sheep for fixed time artificial insemination: improvement of conception rate with a double injection of prostaglandin at 11 days

Abstract: The study investigated, for fixed time artificially inseminated (AI) Menz ewes in field trials, the reproductive performance of prostaglandin-based treatments simultaneously to the standard 'P 4 +eCG' protocol. A total of 483 Menz ewes were assigned to either the 'P 4 +eCG' protocol, using progesterone impregnated intravaginal sponges in combination with equine chorionic gonadotropin (eCG) injection at sponge withdrawal, or the 'PGF s ' treatment where sheep received a single injection of prostaglandin or 'PGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
1
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
1
2
1
2
Order By: Relevance
“…On the other hand, in short intervals, there are altered plasma P4 levels at the end of the luteal phase which may impair the pre-ovulatory actions and the success of conception. (13) Furthermore, our results are in accord with Besufkad et al (14) who found that double PGF 2α , 11 days apart, yielded a greater conception rate and prolificacy when compared with double PGF 2α , 7 days apart.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, in short intervals, there are altered plasma P4 levels at the end of the luteal phase which may impair the pre-ovulatory actions and the success of conception. (13) Furthermore, our results are in accord with Besufkad et al (14) who found that double PGF 2α , 11 days apart, yielded a greater conception rate and prolificacy when compared with double PGF 2α , 7 days apart.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, PGF 2α -14d was successful in inducing 100 % fertile estrus combined with full reproductive success in ewes during the early summer season, supporting the concept that, long-interval double PGF 2α protocols were efficacious in inducing fertile estrus in comparison with short-interval double PGF 2α protocols. (13,14) Further, PGF 2α induces luteolysis which includes functional and structural regression of CL (41) with a decrease in serum P4 level. (42) These findings might be a reasonable explanation for this greater reproductive outcome obtained with the PGF 2α -14d protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La inducción y sincronización del estro en todas las ovejas del estudio se realizó en el mes de marzo, considerado como el periodo de transición de la época reproductiva al anestro estacional (Gündoğan et al, 2003). Según Besufkad et al (2020), la manifestación del estro es la respuesta fisiológica a las aplicaciones de un análogo de prostaglandina o de progesterona (Fierro et al, 2013), en diferentes momentos durante la fase lútea en ovejas con ciclos aleatorios. Las ovejas de la raza Katahdin utilizadas en este estudio tuvieron un valor promedio del 90.3% de estro en los cuatro tratamientos; resultado similar al 94.4% de estro reportado en ovejas Santa Inés y Black Belly de Barbados (Godfrey et al, 1999), al 100% de estro en ovejas Pelibuey (Arroyo et al, 2013) y al 84.2% en ovejas Awassi con dispositivos impregnados de progesterona (Swelum et al, 2018).…”
Section: Discussionunclassified
“…Por su parte, las tasas promedio de prolificidad y fecundidad fueron 1.4 y 1.05, respectivamente; sin diferencias significativas entre tratamientos; valores similares a lo reportado en ovejas de la raza Pelibuey (1.5;Aké-López et al, 2015). Por su parte, Besufkad et al (2020) reportaron una mejora en la prolificidad por efecto de la eCG, la cual contribuyó a un aumento de la tasa de ovulación en ovejas de la raza Menz. Sin embargo, se han reportado valores bajos con la variable prolificidad en ovejas Awassi con el uso de CIDR (1.0;Swelum et al, 2018) y en ovejas Merino australiano al aplicar dos dosis de PGF2α con 7 d de diferencia e IATF (1.0;Olivera-Muzante et al, 2011).…”
Section: Discussionunclassified